HUBUNGAN KADAR HEMOGLOBIN, PARITAS DAN USIA KEHAMILAN DENGAN KEJADIAN KETUBAN PECAH DINI - Lusiana Sinaga, Friska; Samuel Hutasoit, Eka; Anto Pakpahan, Edwin (Jurnal Kedokteran Methodist, 2021)
Background: Maternal mortality rate (MMR) and mortality rate (IMR) are indicators to reflect the health status of mothers and children, as well as a reflection of a country’s health status. According to the 2015 Indonesian Demographic and Health Survey, the maternal mortality rate was 305 / 100.0000 live births. The infant mortality rate based on the 2015 Inter-Census Population Survey was 22 / 100,000 live births. One of the causes is premature rupture of the membranes. Premature rupture of membranes is the rupture of your membranes before signs of labor. Methods: This type of research is a study using the literature method or review literature. This is instrument uses secondary data in the form of publication data obtained from database searches. Conclusion: There was a relationship between hemoglobin levels, parity and gestational age with the incidence of premature rupture of membranes.